The generation of postmemory : writing and visual culture after the Holocaust - Hirsch, Marianne (Columbia University Press, 2012)
Can we remember other people's memories? The Generation of Postmemory argues we can: that memories of traumatic events live on to mark the lives of those who were not there to experience them. Children of survivors and their contemporaries inherit catastrophic histories not through direct recollection but through haunting postmemoriesmultiply mediated images, objects, stories, behaviors, and affects passed down within the family and the culture at large.